Long-term unemployment in Poland in the years 1995-2007 - Eugeniusz Kwiatkowski; Leszek Kucharski (Comparative Economic Research. Central and Eastern Europe, 2009)
This study analyses trends in the long-term unemployment in Poland, as well as its structure and macroeconomic importance for both equilibrium unemployment and the efficacy of anti-inflationary policy. It combines a theoretical part with discussion based on the statistics on the Polish economy for recent years. As shown by the theoretical analysis, long-term unemployment weakly eases wage pressure exerted by workers, so a larger percentage of the long-term unemployed lifts equilibrium unemployment to a higher level and makes anti-inflationary policy less effective. The empirical analyses of the Polish economy indicate that the duration of unemployment is a factor that significantly shapes the probability of finding a job. The hypothesis that the rates of worker flows from the stock of unemployment to the stock of employment are much lower in the case of the long-term unemployed persons than for the short-term unemployed has been corroborated. The statistical data on the Polish economy show that the country's long-term unemployment is relatively large. To curb the negative macroeconomic impacts of this type of unemployment, its scale needs to be reduced. It is also necessary to increase the rate of long-term unemployed workers using the active labour market programmes.
Keywords: 330